Assessing wetland ecosystem services and poverty interlinkages: a general framework and case study - Kumar, R.; Horwitz, P.; Milton, G.R.; Senaratna Sellamuttu, Sonali; Buckton, S.T.; Davidson, N.C.; Pattnaik, A.K.; Zavagli, M.; Baker, C. (Informa UK Limited, 2011)
The wise use of wetlands is expected to contribute to ecological integrity, as well as to secure livelihoods, especially of communities dependent on their ecosystem services for sustenance. This paper provides a conceptual framework capable of examining the goals of wetland management, poverty reduction and sustainable livelihoods. The framework highlights ecological character as a social construct and, with the notion of wetlands as settings for human well-being, builds a concept for assessing the inter-linkages between ecosystem services and livelihoods.The value and broader applicability of our framework is then tested by applying it to a case study from India (Lake Chilika) to evaluate the degree to which the mutual goals of improving both human well-being and the ecological character of wetlands have been achieved. The case study maps changes in human well-being induced in the basin communities due to external vulnerability contexts, institutions and freedoms. It further assesses the response strategies in terms of their impacts on ecological character and poverty status.